Histopathological Changes of Midgut Epithelial Cells of Aedes aegypti Larvae Exposed to Permot Leaf Extract (Passiflora foetida) - Susilowati, Rina Priastini; Sari, Monica Puspa (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
The Aedes aegypti mosquito is the main vector of dengue hemorrhagic fever (DHF). Various prevention efforts were carried out to reduce the population of Ae. aegypti. One way to break the chain of Ae. aegypti is to kill the development of its larvae, namely with synthetic or vegetable larvicides. Permot (Passiflora foetida) is one type of plant that can be used as a vegetable insecticide because it contains active chemical compounds such as alkaloids and flavonoids. Larvae of Ae. aegypti used was instar III with a total of 600, which was divided into 6 treatment groups (1 negative control group, 1 positive control group using 1% temephos, permot leaf extract with dose levels of 0.5%, 1%, 2% and 4% ) and 4 replicates. Data on mortality of Ae. aegypti was calculated to determine the effective dose (LC50 and LC90) using the Probit test, while histopathological changes were calculated to determine the toxicity of the permot leaf extract using the one-way Anova test. The results showed that the LC50 value was 1.85% and LC90 was 2.35%, which means that the effective dose of permot leaf extract was 2.35%. In the treatment of 4% permot leaf extract, it showed histopathological changes in the midgut epithelial cells of Ae. aegypti larvae, midgut epithelial cells became lysed, changed shape, cytoplasmic vacuolization, and separated from the basement membrane. Peritrophic membranes, microvilli and brush border were partially or totally damaged.Â